Cardiac and Vascular Remodeling After 6 Months of Therapy With Sacubitril/Valsartan: Mechanistic Insights From Advanced Echocardiographic Analysis - Monosilio, Sara; Filomena, Domenico; Luongo, Federico; Sannino, Michele; Cimino, Sara; Neccia, Matteo; Mariani, Marco Valerio; Birtolo, Lucia Ilaria; Benedetti, Giulia; Tonti, Giovanni; Pedrizzetti, Gianni; Vizza, Carmine Dario; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Effects of Sacubitril/Valsartan on left ventricular (LV) mechanics and ventricular-arterial coupling in patients with heart failure with reduced ejection fraction (HFrEF) are not completely understood. The aim of this study was to evaluate both cardiac and vascular remodeling in a group of HFrEF patients undergoing S/V therapy. Methods: Fifty HFrEF patients eligible to start therapy with S/V were enrolled. Echocardiographic evaluation was performed at baseline and after six months of follow-up (FU). Besides standard evaluation, including global longitudinal strain (GLS), estimated hemodynamic forces (HDFs) and non-invasive pressure-volume curves (P-V loop) were assessed using dedicated software. HDFs were evaluated over the entire cardiac cycle, in systole and diastole, both in apex to base (A-B) and latero-septal (L-S) directions. The distribution of LV HDFs was evaluated by L-S over A-B HDFs ratio (L-S/A-B HDFs ratio). Based on estimated P-V loop curves, hemodynamic evaluation included left ventricular end-systolic elastance (Ees), arterial elastance (Ea) and ventricular-arterial coupling (VAC) Results: At six months of FU indexed left ventricular end-diastolic and end-systolic volumes decreased (p< 0.001), ejection fraction (p< 0.001) and GLS (p < 0.001) significantly improved. Re-alignment of HDFs occurred, with a reduction of diastolic L-S/A-B HDFs ratio (p< 0.001). A reduction of Ea (p=0.008) and an improvement of Ees (p< 0.001) and VAC (p< 0.001) were observed. Conclusion: S/V therapy leads to a complex phenomenon of reverse remodeling involving increased myocardial contractility, HDFs distribution improvement, and afterload reduction.